Unveiling the Beauty of Figurative Language: A Stylistic Analysis of Qur’an Surah As-Saffat and Ar-Rahman in Abdullah Yusuf Ali’s Translation - Dinar Dipta; Norhayati binti Haji Abd Karim; Diska Fatima Virgiyanti; Eka Indah Nuraini; Aries Fachriza; Aniesa (Al-Lisan: Jurnal Bahasa)
Background: Figurative language deals with non-literal language to shift meaning by comparing other words to the original composition. This appears in many works of literature, including the holy Qur’an. Therefore, it is essential to study, not intending to reduce or increase the meaning of the Qur’an.